Creating a Language and Literacy Space for Long-Term English Learners: A Transformative Approach - Simpson, Helen Lanning Gaskill (East Carolina University)
Researchers in the fields of second language acquisition, linguistics, and adolescent literacy have grappled with how to define long-term English learner status, identify their characteristics, and effectively develop their academic language and literacy skills. Foundational to this study, long-term English learner perceptions provided a qualitative window into their in-school academic reading and language development experiences. This qualitative data informed and augmented the design of a literacy and language co-teaching intervention based on the ExC-ELL literacy framework. The co-taught intervention leveraged the skills of an English language arts teacher and the English language development specialist to strengthen academic reading comprehension and academic language. Quantitative data from the intervention yielded some amelioration in reading comprehension. In contrast, academic language results were varied across the individual students. By focusing on English learners' linguistic assets, this study began to shift the broad-brush deficit perspective of long-term English learners at the school level previously perpetuated by deficient academic outcome data. On a more global level, the study challenged ESSA-mandated policy, appealing for alignment of state-defined annual language growth targets with second language acquisition research. This study adds to the scholarship on long-term English learners heretofore largely situated in metropolitan areas of New York, California, and Texas, as well as an expansive quantitative study of 41 states in the WIDA Consortium. The inquiry cast a tightly focused lens on a rural middle school setting, illuminating long-term English learners' literacy and language practices and illustrating both learner agency and individualized need. A pathway forward to further research may be to build on both long-term English learners' existing literacy practices and linguistic assets in order to develop agentive readers and language learners.
Keywords: long-term English learner; adolescent literacy; English language--Study and teaching--United States--Foreign speakers; Academic language--Study and teaching--United States; Rural schools--United States